Pro-Life Activism, Abortion and Subjectivity Before Birth: Discursive Practices and Anthropological Perspectives - Mattalucci, Claudia (Mediterranean Journal of Social Sciences, 2012)
This paper is intended as a critical examination of pro-life discursive practices. It is based on ethnographic researchconducted in Lombardia (northern Italy) among a group of pro-life activists. Pro-life activism in Italy has a predominantly Catholicmatrix and subjects who participated in my research mainly come from a Catholic background. However, their discursivestrategies are not framed in religious terms. Although informed by ethical concerns, pro-life activists make a great use ofscientific material (images and descriptions of intrauterine development) to advocate their idea of the fetus as a human beingwith a right to life and to prove that subjectivity precedes birth. In this paper I consider the empirical and theoretical implicationsof the overlapping of moral issues and scientific knowledge. On one hand, pro-life activists emphasize the similarities betweenthe fetus and the newborn child; they also attribute the unborn some of the characteristics of the Western-informed notion ofperson: individuality, autonomy, the ability to communicate and interact, and some form of consciousness. I argue that thedefinition of fetus as person relies on a teleology of vital processes that presupposes a specific moral order. On the other hand,pro-life discursive practices allow to reconsider the uses of the Western idea of the person at the margins of human life and toarticulate a critical approach to the biologization of the abortion debate.